Undergraduate Software Engineering. - LUTZ, MICHAEL J.; NAVEDA, J. FERNANDO; VALLINO, JAMES R. (Communications of the ACM, 2014)
The authors discuss reasons why an undergraduate software engineering degree is needed to provide an educational experience that prepares students better for careers in the software industry. Topics addressed include the Rochester Institute of Technology's (RIT) launch of the first U.S. undergraduate software engineering program in 1996, the state of software engineering in the computer science curriculum, and comparisons between horizontal and vertical curricula. also mentioned are the benefits of active learning and team-based project work, and assessing the effectiveness of RIT's software engineering program.